Hubungan Kemampuan Membaca Pemahaman dengan Kemampuan Menulis - Zartika Nofitri; Ena Noveria (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
ABSTRACTThis article generally aims to determine the ability to read with the ability to write, while specifically to get an idea of the relationship between reading and writing in writing an article. The ability to reading comprehension and write has a very close relationship when viewed from various aspect. This certainly happens because there is continuity between the two language skills. A writer will not be able to produce a good writing if unable and skilled in reading. Skillful in reading here means being able to understand the contents of the reading and know the meaning of the reading. Vice versa, if someone is skilled in reading then he will easily produce an article. Kata kunci: kemampuan, membaca, menulis